ENCOURAGING THE INTENTION TO USE MOBILE JKN APPLICATION FOR PATIENT REGISTRATION AND APPOINTMENT IN INDONESIA: A CROSS-SECTIONAL STUDY - Pratama, Zain Syafrudin; Suhartanto, Dwi (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: The Muhammadiyah Bandung Hospital is grappling with substantial obstacles in delivering healthcare services, notably in the domain of patient registration. A critical concern is the burgeoning queues stemming from offline admissions processes. Notably, the utilization of Mobile JKN for registration is markedly low, despite its potential to mitigate these issues. Purpose: The objective of this research is to identify the determinants that shape outpatients’ intentions to employ Mobile JKN for online registration and scheduling. The aim is to foster and augment the adoption of Mobile JKN for outpatient services at the Muhammadiyah Hospital in Bandung. Methods: Employing the modification of Unified Theory of Acceptance and Use of Technology (UTAUT) framework, and incorporating satisfaction as an additional variable, this study analyzed survey data from 426 outpatients at Muhammadiyah Bandung Hospital using Structural Equation Modeling (SEM) to assess the interplay among the variables. Results: Findings reveal that Social Influence (SI), Trust (T), and Satisfaction (S) exert a direct and substantial impact on the intention to utilize Mobile JKN. Conversely, performance expectancy (PE), effort expectancy (EE), facilitating conditions (FC), and perceived risk (PR) were found to have no significant influence on the intention to use Mobile JKN. Conclusion: These insights provide actionable guidance for healthcare service providers, particularly at Muhammadiyah Bandung Hospital and similar institutions, to enhance their understanding of outpatient behaviors in relation to the adoption of Mobile JKN for online registration and appointment scheduling.